The Topmost Gold Deposits in China in the Part of the Northwest Pacific Rim with Emphasis on Gold Prospecting (The Australasian Institute of Mining and Metallurgy, 1990)
Gold mineralization belt of eastern China in the adjacent part of the northwestern Pacific rim is orientated NE to NNE and as-sociated with Mesozoic faults and igneous intrusives and Mesozoic to Cenozoic volcanism and subvolcanism extending more than 3000 km in length and 300 to 800 kni in width affected by the movement from the Pacific Plate subducted against the Asian Plate.The relative movement between the Pacific and the Asian plates give rise to two types of fracture zones, the tensional ones providing the space for the formation of fissure-filling type of auriferous quartz veins and the shear zones providing the space for the formation of hydrothermal replacement type of gold de-posits in Shandong Peninsula. The fissure filling type of quartz vein, is represented by Linglong gold deposit which is hosted in Mesozoic Linglong Granite and consists of hundreds of quartz veins filling fractures trending NE to NNE and the hydrothermal replacement type is represented by Sanshandao gold deposit which is hosted in crushed and hydrothermally altered Mesozoic Linglong Granite in contact with Archaean metamorphic complex of Jiaodong Group along a Mesozoic upthust fault zone trending NE.